40 days of love we were made for relationships. - Warren, Rick, 1954-; Saddleback Church ([Lake Forest, CA] : Saddleback Church : Distributed by Zondervan, 2009)
"A six-session video-based study for small groups"--Container.
DVD ; NTSC all regions.
Closed captioned for the hearing impaired.
Taught by Rick Warren.
"This DVD is designed to be used with the 40 Days of Love Video Study Guide (ISBN: 9780310326878)"--Container.
Keywords: Christian life; Christian life; Video recordings for the hearing impaired